2007
DOI: 10.1016/j.apergo.2006.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Association between objective and subjective measurements of comfort and discomfort in hand tools

Abstract: In the current study the relationship between objective measurements and subjective experienced comfort and discomfort in using hand saws was examined. 12 carpenters evaluated five different hand saws. Objective measures of contact pressure (average pressure, pressure area and P-t integral) in static and dynamic conditions, muscle activity (EMG) of five muscles of the upper extremity, and productivity were obtained during a sawing task. Subjective comfort and discomfort were assessed using the Comfort Question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
52
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(56 citation statements)
references
References 25 publications
3
52
0
1
Order By: Relevance
“…The diverging results might be due to differences between the studied tasks, including differing requirements for speed and acceleration. In the present study, the increased work pace did not result in additional shoulder movement and thus no additional requirements were put on the trapezius muscle for this reason (Kuijt-Evers et al 2007). Also, the more forward, 'engaged' upper body posture during the HWP reduced the external gravitational torque on the moving arms, leading to a smaller force required from the muscles to support the arms.…”
Section: Work Pace and Exposure Levelsmentioning
confidence: 74%
“…The diverging results might be due to differences between the studied tasks, including differing requirements for speed and acceleration. In the present study, the increased work pace did not result in additional shoulder movement and thus no additional requirements were put on the trapezius muscle for this reason (Kuijt-Evers et al 2007). Also, the more forward, 'engaged' upper body posture during the HWP reduced the external gravitational torque on the moving arms, leading to a smaller force required from the muscles to support the arms.…”
Section: Work Pace and Exposure Levelsmentioning
confidence: 74%
“…By improving the ergonomics and usability of hand tools, work efficiency, productivity and quality, as well as user comfort and safety can be improved (Buchholz et al, 1992;Kadefors et al, 1993;Kardborn, 1998;Kilbom et al, 1993;Kuijt-Evers et al, 2004, 2007Meagher, 1987;Sperling et al, 1993;Tudor, 1996;You et al, 2005). Ergonomically well-designed hand tools used in work situations with balanced work content reduce the risk of occupational injuries of the hand, wrist and forearm .…”
Section: Introductionmentioning
confidence: 96%
“…It has been demonstrated that by improving the ergonomic quality of hand tools as well as comfort, it is possible to increase work productivity Kuijt-Evers et al, 2007). This is also important from the viewpoint of workers' health because they normally use tools with the highest productivity, even at the cost of a higher degree of strain and fatigue Kilbom et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Tool handle design research has been previously limited to the determination of the diameters of cylindrical handles to increase performance and comfort for reducing the chances of CTD (i.e., blisters, inflamed skin, cramped muscles, etc.) [1][2][3][4]. Many studies have researched the topic of tool handle design to define the optimal size and shape of a tool handle.…”
Section: Introductionmentioning
confidence: 99%